Characterisation and computational modelling of high temperature cyclic viscoplastic behaviour of turbine steel - Rae, Yaroslav (2020)
The aim of the research was to investigate the cyclic plasticity behaviour of a turbine rotor steel through experiments and to simulate low cycle creep-fatigue using a finite element (FE) modelling framework of materials and structures.